Tackling Disability of Speech due to Stroke: Perspectives from Stroke Caregivers of the University Teaching Hospital in Zambia - Chiluba, Brian Chanda (The Center for Disability Studies and Services Brawijaya University, 2019)
Many stroke survivors usually have permanent disability such as aphasia, which results in the need for support from caregivers. Care required for stroke survivors differs depending on the type of stroke but there is little research done in this regard. However, current literature provides evidence that support services and interventions for caregivers, especially in relation to managing affective symptoms, are unsatisfactory. The aim of this study was to explore the experiences of caregivers handling aphasic stroke patients at the University Teaching Hospital. An explorative study utilizing qualitative phenomenological approach was utilized with sample of 15 participants who by purposeful sampling were drawn and using thematic method of analysis. This study found that caregivers go through a lot of things in caring for their loved ones and their experience involve a complicated and sometimes unpredictable interplay of multiple processes. Lack of preparedness in assuming the role of caregiving caused the caregivers to go through what seemed to be insurmountable challenges. There is therefore need of caregiver education so that they can deliver appropriate care to the stroke survivors.